Effect of Mobile Phone Use on Blink Rate among MBBS Students in Kathmandu - Mishal, Anu; Giri, U; Rizyal, A (Nepal Medical College Journal, 2021)
Mobile devices such as smart phones and tablets are used globally for checking email, internet browsing, watching videos and posting on social media. A recent survey estimated that, by 2020 shipment of mobile phones will add up to 1.71 billion and a total of around 2.53 billion which constitutes almost one third of the world population owning a smart phone. According to American Optometric Association, 90% of employees who use computers for at least three hours a day experience some vision problem. A reflex that closes and opens eyelids is known as blink, which helps in spreading tears over the conjunctiva and thereby keeping it moist. The normal blinking rate at rest is 17 blinks/min, during conversation it increases to 26 blinks/min, and it is as low as 4.5 blinks/min while reading. Prolong use of mobile phone affects the blink rate. A descriptive cross-sectional study was conducted among MBBS students at Nepal Medical College and Teaching Hospital to find out the effect of mobile device use on blink rate. The age of these students were from 19 to 26 year, with an average of 21.34 years. The result of this study shows that for male students, an average 3.8hr/per day use of mobile phone decreases the blink rate by 53.33 % while watching videos and 80% while reading articles. Similarly, for female students, an average 3.5hr/per day use of mobile phone decreases the blink rate by 31.25% while watching videos and 62.50% while reading articles.